2004
DOI: 10.1080/00480169.2004.36408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stocking density on the performance, carcass characteristics and selected welfare indicators of broiler chickens

Abstract: The data showed that the relationship between stocking density and productivity traits was not linear in nature, in accordance with other studies. Under the conditions of the current study, the performance, mortality and carcass characteristics of broilers grown at densities of 10, 15 and 20 birds per m2 were similar. There were some welfare implications at high population densities as indicated by adverse effects on litter quality, gait scores and the incidence of hock and foot pad burns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
97
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 14 publications
15
97
2
3
Order By: Relevance
“…Imaeda (2000) reported that along with an increase in the number of broilers per square metre, especially in summer months elevated ammonia levels in the air caused death as a result of ammonia poisoning. It was found that broiler density per unit area did not impact mortality in this study and similar findings were confirmed in other studies (Thomas et al 2004;Onbasilar et al 2008). Limited feeding program using in the Pf groups reduced BW and WG during all production period compare to ad libitum fed birds.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Imaeda (2000) reported that along with an increase in the number of broilers per square metre, especially in summer months elevated ammonia levels in the air caused death as a result of ammonia poisoning. It was found that broiler density per unit area did not impact mortality in this study and similar findings were confirmed in other studies (Thomas et al 2004;Onbasilar et al 2008). Limited feeding program using in the Pf groups reduced BW and WG during all production period compare to ad libitum fed birds.…”
Section: Resultssupporting
confidence: 79%
“…However, in general, references indicate that increasing the number of birds per unit depresses growth rate and FI (Thomas et al 2004;Muniz et al 2006;Sahin et al 2007). In this study, the size of pens, feeder and drinker space and location were identical in all pens.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…An ideal litter material should be dry with high water absorption capacity, but should also be able to release the absorbed moisture quickly [6] . Litter material and therefore the quality of litter directly affects the performance, health, carcass quality, and welfare of poultry [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Moreira et al (2004), evaluating three housing densities (10, 13, or 16 broilers/m 2 ), observed significant reduction in weight gain in birds housed at 10 and 16 birds/ m 2 . Mortari et al (2002) also reported reduced body weight as rearing density increased, and Thomas et al (2004), Dozier et al (2005a) *significant at 5%; **significant at 1%; means followed by different lowercase letters within a column are statistically different; means followed by different uppercase letters within a row are statistically different.…”
Section: Resultsmentioning
confidence: 99%